Challenges in non-point source pollution — Sampling and testing - Al-Mamun, Abdullah; Salleh, Md. Noor (2014)
Point pollution sources are usually noticeable, confined and the pollution loads are relatively easy to estimate. Therefore, the treatment technologies can be easily applied to abate pollution from the point sources (PS). On the contrary, non-pointsource (NPS)pollution is generated due to precipitation process, and it is usually difficult to estimate the pollution loadings compared to the PS. For the same location, more runoff means possibility of generating more pollution loads. The humid tropical regions, such as Malaysia, have higher susceptibility to non-point source pollution, both for rural and urban areas. Contribution of pollutants from non-point sources to the rivers is unsteady and very site-specific. Therefore, it is very important to conduct local study; for which a significant number of rainfall events must be properly sampled and tested for the necessary NPS pollutants. Now, the challenges in monitoring NPS pollution is not only chasing the storm events but also identification of safe and representative sampling locations, catchments, selection of relevant runoff quality parameters, acceptable test procedures, etc. There is no doubt that unlike the sampling for point source pollution monitoring, the NPS pollution study requires more logistical support. This paper discusses about the preparations necessary for meaningful and representative NPS pollution study or project in terms of sampling and testing requirements. Sampling requirements for the study of “first flush” phenomenon and determination of “event mean concentration” (EMC) values are also discussed in the paper.